2018
DOI: 10.21865/ridep46.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Equivalencia Factorial De La Escala De Actitudes Hacia La Autoridad Institucional en Adolescentes (Aai-A) Chilenos Y Colombianos

Abstract: ResumenEl propósito de esta investigación fue estudiar la equivalencia y estabilidad psicométrica de la Escala de Actitudes hacia la Autoridad Institucional (AAI-A) en adolescentes chilenos y colombianos. Se realizó un estudio de corte transversal en el que participaron dos muestras independientes de adolescentes de ambos sexos, de edades comprendidas entre 12 y 20 años. La primera muestra estuvo compuesta por 692 adolescentes chilenos, y la segunda por 541 adolescentes colombianos. Los resultados obtenidos me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
2
4
0
5
Order By: Relevance
“…The results of this investigation showed that the general factor of the SCASIM-St15 called School Climate and the School Identification factor presented significant and negative correlations with the Positive Attitude to Transgression factor, but significant and positive correlations with the Positive Attitude to Authority factor. These results are consistent with previous studies which suggest that students who present high levels of transgression of norms, in turn present relational problems in schools ( Gálvez-Nieto et al, 2018 ), and violence toward their parents ( Martínez-Ferrer et al, 2018 ; Del Moral et al, 2019 ). On the other hand, a positive attitude toward the norms of institutions such as the school or the police favors academic success ( Trinidad, 2020 ) and psychosocial adjustment in other social contexts ( Bonilla et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this investigation showed that the general factor of the SCASIM-St15 called School Climate and the School Identification factor presented significant and negative correlations with the Positive Attitude to Transgression factor, but significant and positive correlations with the Positive Attitude to Authority factor. These results are consistent with previous studies which suggest that students who present high levels of transgression of norms, in turn present relational problems in schools ( Gálvez-Nieto et al, 2018 ), and violence toward their parents ( Martínez-Ferrer et al, 2018 ; Del Moral et al, 2019 ). On the other hand, a positive attitude toward the norms of institutions such as the school or the police favors academic success ( Trinidad, 2020 ) and psychosocial adjustment in other social contexts ( Bonilla et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the adapted version of the Attitudes to Institutional Authority in Adolescence Scale (AIA-A) was applied ( Gálvez-Nieto et al, 2018 ). The AIA-A is a self-report scale that assesses adolescent attitudes toward authority figures, has nine items and is answered using a five-point ordinal scale (1 = Never, 5 = Always).…”
Section: Methodsmentioning
confidence: 99%
“…Future lines of enquiry could assess associations with other constructs linked to the school setting. In this context, it would be interesting to see the effect of school climate on school regulations ( Gálvez-Nieto et al, 2015b ) or explanatory studies that analyze the relationships between the various ecological aspects of the school system ( Bronfenbrenner, 2002 ; Gálvez-Nieto et al, 2020 ). This study highlights the need to carry out psychometric studies in order to estimate the stability of school climate measurements over time and to analyze the invariability of the construct in other populations of Spanish-speaking students, with the aim of facilitating the comparison of results between different cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo como se señaló anteriormente, intervenir en estas variables, no solo permitirá favorecer el desarrollo de los estudiantes en este ámbito, sino que posibilitará la mejora de las relaciones interpersonales entre los estudiantes, así como el incremento de las expectativas académicas de la familia (Calero et al, 2014;Gálvez-Nieto, Vera-Bachmann, Trizano, & García, 2015).…”
Section: Discussionunclassified